Case Report: Posterior Reversible Leukoencephalopathy Syndrome (PRES) as a Biologically Predictable Neurological Association in Severe COVID-19. First Reported Case From Australia and Review of Internationally Published Cases - Wijeratne, Tissa; Wijeratne, Chanith; Karimi, Leila; Sales, Carmela; Crewther, Sheila Gillard (Frontiers in Neurology, 2021)
Reports of different types of neurological manifestations of COVID-19 are rapidly increasing, including changes of posterior reversible leukoencephalopathy syndrome (PRES). Here we describe the first reported case of COVID-19 and PRES in Australia diagnosed on basis of MRI brain imaging and confirmed clinically by presence of confusion, delirium, headaches, also associated with hypertension and blood pressure variability and stable long-term kidney problems. He made full recovery as his blood pressure was controlled and clinical status was supported with appropriate supportive therapy. Although traditionally a rare condition, PRES is likely to be more common among patients with COVID-19 pathobiology there is Renin downregulation of ACE2 receptors, involvement of Renin-Angiotensin-Aldosterone system, endotheliitis, cytokine storm, and hyper-immune response. Thus we advocate clinical suspicion and early brain imaging with MRI brain among vulnerable patients with known co-morbidities, and diagnosed with COVID-19 given that hypertension and blood pressure variability are often exacerbated by acute SARS-CoV-2 immune reactions. Such acute hypertensive encephalopathy was able to be reversed with timely supportive therapy ensuring re-hydration and re-establishment of blood pressure control.